Development of surface functionalized microfiber sensors for heavy metal detection in aqueous environment - Zhang, Ying (2016)
Nowadays, water contamination by heavy metals is still a serious environmental problem encountered in many areas, especially some developing countries. Pollution has destroyed eco-systems of some water areas and also threatened our health. Developing a fast and effective method to detect heavy metals in water is essential to eliminate environmental pollution and to ensure that our drinking water is suitable for consumption. As the development of micro/nanotechnology, microfiber sensor has become a new trend for optical sensing due to its fast response and higher sensitivity. Both tapered microfiber sensors and microfiber long period grating (LPG) sensors demonstrate good sensitivity for refractive index (RI) sensing of the fluid surrounding the fiber. In this project, these two kinds of microfiber RI sensors were explored to detect the concentration of heavy metal solutions in water. In order to improve the sensors’ sensitivity and also make the detection more specific to a particular element, we functionalized the surface of the fibers’ sensing region with a silane APTES and then a special chemical called EDTA. EDTA is a chelating agent which can trap metals, such as zinc, copper and lead. Different metals surrounding the fibers have different RI. Thus the developed surface-functionalized sensor can detect the different kinds of heavy metals. To verify that the surface is properly functionalized, XPS was used to characterize the fiber surface after functionalization. The result shows a successful attachment of APTES and EDTA. Both tapered microfiber and microfiber LPG sensors were fabricated, functionalized and investigated for heavy metal detections. The experiments show that tapered microfiber sensor undergoes 5.1 nm and 13.5 nm wavelength shifts for the 10 ppm ZnCl2 and CuCl2 solutions respectively. Microfiber LPG sensor doesn’t show significant results for the ppm level ion detection. This is probably due to thick cladding layer, and hence weak evanescent wave in the surrounding fluid, and relatively low RI sensitivity compared to the tapered microfiber sensors.